Biocompatibility, bioactivity, porosity, and sealer/dentin interface of bioceramic ready-to-use sealers using a dentin-tube model - Inada, Rafaela Nanami Handa [UNESP]; Silva, Evelin Carine Alves [UNESP]; Lopes, Camila Soares [UNESP]; Queiroz, Marcela Borsatto [UNESP]; Torres, Fernanda Ferrari Esteves [UNESP]; da Silva, Guilherme Ferreira; Cerri, Paulo Sérgio [UNESP]; Guerreiro–Tanomaru, Juliane Maria [UNESP]; Tanomaru-Filho, Mário [UNESP] (Springer Nature, 2024)
This study evaluated the biocompatibility, bioactivity, porosity, and sealer/dentin interface of Sealer Plus BC (SP), Bio-C Sealer (BIOC), TotalFill BC Sealer (TF), and AH Plus (AHP). Dentin tubes filled with the sealers and empty tubes (control group) were implanted in the subcutaneous tissue of rats for different periods (n = 6 per group/period). Number of inflammatory cells (ICs), capsule thickness, von Kossa reaction, interleukin-6 (IL-6) and osteocalcin (OCN) were evaluated. Porosity and voids in the interface dentin/sealers were assessed by micro-computed tomography. The data were submitted to ANOVA/Tukey’s tests (α = 0.05). Greater capsule thickness, ICs and IL-6 immunolabeling cells were observed in AHP. No significant difference in thickness of capsule, ICs, and IL-6- immunolabeling cells was detected between SP and TF, in all periods, and after 30 and 60 days between all groups. At 60 days all groups had reduction in capsule thickness, ICs and IL-6 immunolabeling cells. Von Kossa-positive and birefringent structures were observed in the capsules around the sealers. BIOC, SP, and TF exhibited OCN-immunolabeling cells. All sealers had porosity values below 5%, besides low and similar interface voids. BIOC, SP and TF are biocompatible, bioactive, and have low porosity and voids. The dentin-tube model used is an alternative for evaluating bioceramic materials.